Peran UMKM Dalam Menanggulangi Kemiskinan Di Provinsi Kalimantan Tengah - Tari Angriani; Junita Perangin Angin; Ira Veronika Girsang; Dedi Takari (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research aims to understand the impact of the number of Micro, Small and Medium Enterprises (MSMEs) and the workforce involved in the MSME sector on poverty levels in Central Kalimantan. Through this research, it is hoped that we can increase understanding and knowledge about the factors that contribute to efforts to reduce poverty. The data used in this research consists of secondary data covering a five year period, starting from 2018 to 2022. The research method applied is the quantitatively to analyze the relationship between the independent variables, namely the number of MSMEs (X1) and the MSME sector workforce (X2), with the dependent variable, namely the number of poverty (Y). The large number of poverty can be influenced by Micro, Small and Medium Enterprises (MSMEs) because MSMEs have an important role in creating jobs, supporting economic growth and reducing economic inequality. From this research, it is concluded that the number of Micro, Small and Medium Enterprises ( MSMEs) in Central Kalimantan Province do not significantly influence factor Y, which shows that the number of MSMEs in the region does not play a role in reducing poverty levels. Meanwhile, the variable number of workers apparently has a significant impact on the poverty level in Central Kalimantan Province.